Impact of contralateral sensorineural hearing loss on prognosis in idiopathic sudden sensorineural hearing loss - Sanlin Xie; Zhifeng Chen; Lipeng Huang; Yongjun Hong; Chang Lin (PLoS ONE, 2026)
Objective The aim of this study was to investigate the impact of contralateral sensorineural hearing loss on prognosis in idiopathic sudden sensorineural hearing loss. Methods A retrospective analysis was conducted on 445 ISSNHL patients treated between January 2020 and January 2024. The patients were divided into two groups: recovery (234 cases, including complete and partial recovery) and no-recovery (211 cases, no recovery). Pure-tone audiometry was used for evaluation. Clinical characteristics were compared between the groups, and multivariate logistic regression was performed to identify risk factors for poor prognosis. Results Significant differences were observed between the two groups regarding contralateral hearing level, age, duration of illness, diabetes, hypertension, and audiometric curves. An increase in the hearing threshold of the contralateral ear was positively correlated with the risk of ineffective treatment. Patients with contralateral sensorineural hearing loss prior to the onset of ISSNHL exhibited a 2.757-fold increased risk of treatment failure compared with ISSNHL patients who had normal contralateral ear hearing. Multivariate logistic regression analysis revealed that contralateral sensorineural hearing loss exhibited a significant multiplicative interaction with age over 60 years, hypertension, and a disease duration exceeding 4 days. Conclusion The presence of contralateral sensorineural hearing loss before the onset of ISSNHL is an independent risk factor for poor prognosis in ISSNHL. It interacts significantly with age over 60 years, hypertension, and disease duration exceeding 4 days. A thorough assessment of contralateral hearing status, in conjunction with factors such as age, hypertension, and disease duration, is essential for developing personalized treatment plans to improve prognosis.